"Unity in harmony": nationalism and national identity in the works of selected South and Southeast Asian writers - Quayum, Mohammad Abdul (2015)
This paper seeks to investigate the discourses of nationalism and national identity in the works of six Asian writers, three from South Asia and three from Southeast Asia. The South Asian writers to be discussed include Rabindranath Tagore (1861-1941), Rokeya Sakhawat Hossain (1880-1932) and Kazi Nazrul Islam (1899-1976), while the Southeast Asian writers will include Lloyd Fernando (1926-2008), Adibah Amin (1936-) and Shirley Lim (1944-). The objective is to argue that although these writers wrote from different socio-political-cultural circumstances and historical periods, they all largely recommend a similar vision of nationalism and national identity for the society they represent/represented, whether it be colonial India or colonial/postcolonial Malaya/Malaysia. They all rejected a monocular, unilateral and exclusive view of national identity in favour of multiculturalism, multilateralism and inclusivism, and spurned “unity in uniformity” in support of “unity in harmony,” where cultures could co-exist in a spirit of sharing and mutual respect rather than being inimical, hierarchical or hostile towards one another. The discussion will focus on a body of Tagore’s writings, selected essays and stories by Rokeya, Nazrul’s third and final novel Kuhelika (Mystery; 1932, translated 2015), Lloyd Fernando’s second novel Green is the Colour (1993), Shirley Lim’s first novel Joss and Gold (2001) and Adibah Amin’s novel This End of the Rainbow (2013) – the symbol in the last title being quintessentially representative of all the works to be discussed in this paper.